Atypical case of Heck’s disease in a healthy adolescent from Ecuador. Case report - Buele Lanchi , Cristopher Oswaldo (2024)
The aim of this article is to report an atypical case of Heck's disease, given its single-site positivity for HPV genotypes 56, 71 and 74, with different biological significance. This disease is a benign oral pathology with variable prevalence according to geographic region and ethnic group; its etiology is multifactorial, in which the human papillomavirus (HPV), genotypes 13 and 32 play a leading role. However, in the last ten years, sporadic cases of this pathology have been documented, positive for non-classical genotypes and high oncogenic risk. The clinical and histopathological picture found in the patient's oral cavity was consistent with the entity in reference, confirmed by a molecular study based on polymerase chain reaction for HPV genotypes 56, 71 and 74. In conclusion, the present case is considered unusual due to positivity for genotypes that have not been documented in this pathology until now. Thus, clinical criteria (age, ethnicity, personal and family medical history, clinical signs) are key when making a presumptive diagnosis, and histopathology is essential in the definitive diagnosis of this entity, through the search for mitosoid bodies.